EXTRACT AND ISOLATE ACTIVITIES FROM KECOMBRANG (ETLINGERA ELATIOR (JACK) R. M. SMITH) AS INHIBITOR OF TYROSINASE ENZYME - Muslihin, Nisrina
Hyperpigmentation is a common skin pigment disorder due to a cumulative increase in the amount and distribution of melanin in the epidermis and dermis. Inhibiting the formation of melanin is one way that can be done to brighten the skin. Kecombrang (Etlingera elatior) is a family of Zingiberaceae to Indonesia which is reported to have the potential to inhibit tyrosinase enzymes in the leaves, flowers, and fruits of kecombrang. Purpose: The purpose of this study was to determine the activity of the ethanol extract of kecombrang leaves, flowers, and fruits in inhibiting the tyrosinase enzyme, to isolate the compound, and to identify and test the activity of the isolates in inhibiting the tyrosinase enzyme. Method: The extraction used is maceration using ethanol. Fractionation was carried out using the liquid-liquid extraction method. Activity test was carried out quantitatively and qualitatively. Quantitative activity was tested by determining the percent inhibition value of each sample. Qualitative activity test using the bioautographic method. The search for active compounds begins with testing the ethanol extracts of kecombrang leaves, flowers, and fruits. The selected extracts then proceed to the fractionation stage using the liquid-liquid extraction method, followed by column chromatography, each process monitored by TLC. Results: The inhibitory activity of the ethanol extracts of leaves, flowers, and fruits of E. elatior at a concentration of 500 µg/mL were 69,96±1,56%, 19,39±1,29 %, and 10,69±1,54%respectively, so the ethanol extract of E. elatior leaves was continued to the fractionation stage. The n-hexane, ethyl acetate, and water fractions with inhibitory activity respectively at a concentration of 500 µg/mL were 55,30±2,15%, 29,49±0,62% and 17,01±2,6%. The n-hexane fraction was continued to the separation stage using column chromatography and it was found that the activity of isolate 3 was stronger than isolates 1 and 2 with the percent inhibition of the tyrosinase enzyme at a concentration of 500 µg/mL of 25,4 ± 2,16%. Conclusion: The tyrosinase enzyme inhibitory activity of the ethanol extract of the leaves was stronger than the ethanol extract of the flowers and fruits of E. elatior. Isolate 3 had stronger tyrosinase inhibitory activity than isolates 1 and 2. Based on the identification, it was suspected that isolate 3 was a phenol group compound.